Does High Cerebral Microbleed Burden Increase the Risk of Intracerebral Hemorrhage After Intravenous Tissue Plasminogen Activator for Acute Ischemic Stroke?. Issue 1 (January 2019) - Arca, Karissa N.; Demaerschalk, Bart M.; Almader-Douglas, Diana; Wingerchuk, Dean M.; O'Carroll, Cumara B.
Abstract : Background: The risk of developing intracerebral hemorrhage (ICH) after the administration of intravenous tissue plasminogen activator for acute ischemic stroke is well established in the general population. However, the risk associated with stroke thrombolysis in patients with a history of cerebral microbleeds (CMBs) is undetermined. Objective: The main objective of this study was to critically assess current evidence with regard to the risk of development of ICH after the administration of intravenous tissue plasminogen activator for acute ischemic stroke in patients with CMBs. Methods: The objective was addressed through the development of a critically appraised topic that included a clinical scenario, structured question, literature search strategy, critical appraisal, assessment of results, evidence summary, commentary, and bottom-line conclusions. Participants included consultant and resident neurologists, a medical librarian, clinical epidemiologists, and content experts in the field of vascular and hospital neurology. Results: A recent individual patient data meta-analysis was selected for critical appraisal. Cohorts were analyzed with pretreatment magnetic resonance imaging to determine CMB burden and were followed-up to assess subsequent symptomatic ICH, hemorrhagic transformation, parenchymal hemorrhage (PH), and remote PH (PHr) following intravenous thrombolysis. Risk of symptomatic ICH, PH, and PHr was increased in the presence of CMBs, with PHr having the strongest association with increasing CMB burden. Only patients with >10 CMBs were found to have associations with poor outcome at 3 to 6 months, whereas there was no association with 3 to 6 months' mortality. Conclusions: CMBs are associated with an increased risk of postthrombolysis ICH; however, the clinical implications have yet to be determined.